Anticoagulant rodenticides in Strix owls indicate widespread exposure in west coast forests. (October 2019) - Wiens, J. David; Dilione, Krista E.; Eagles-Smith, Collin A.; Herring, Garth; Lesmeister, Damon B.; Gabriel, Mourad W.; Wengert, Greta M.; Simon, David C.
Abstract: Exposure of nontarget wildlife to anticoagulant rodenticides (AR) is a global conservation concern typically centered around urban or agricultural areas. Recently, however, the illegal use of ARs in remote forests of California, USA, has exposed sensitive predators, including the federally threatened northern spotted owl ( Strix occidentalis caurina ). We used congeneric barred owls ( S. varia ) as a sentinel species to investigate whether ARs pose a threat to spotted owls and other old-forest wildlife in northern regions of the Pacific Northwest. We analyzed the liver tissue from 40 barred owls collected in Oregon and Washington and confirmed exposure to ≥1 AR compounds in 48% of the owls examined. Brodifacoum, an extremely toxic second-generation AR, was the most common compound detected (89% of positive cases), followed by bromadiolone (11%), difethialone (11%), and warfarin (5%). Brodifacoum was also detected in one barred owl and one spotted owl opportunistically found dead (liver concentrations were 0.091 and 0.049 μg/g, respectively). We found no evidence that exposure varied with proximity to developed and agricultural areas, or among different study areas, age-classes, and sexes. Rather, exposure was ubiquitous, and the rates we observed in our study (38–64%) were similar to or greater than that reported previously for barred owls in California (40%). Together these studies indicate widespread contamination in forested landscapes used by spotted owls and other wildlife of conservation concern. Owls collected in older forests may have been exposed via illegal use of ARs, highlighting a mounting challenge for land managers and policy makers. Highlights: Anticoagulant rodenticides were detected in 48% of barred owls sampled in old-growth forests. Brodifacoum was the most common rodenticide detected (89% of positive cases). Exposure was ubiquitous across three study areas in Oregon and Washington. Illegal use of rodenticides near protected forests was a likely source of exposure.